Visual Secrete Sharing by Diverse Image Media (International Journal of Engineering and Computer Science, 2017)
Conventional visual secret sharing schemes hide secret images in shares and the image may be printed on transparencies or encoded and also stored in a digital form. The shares of the image can appear like noise pixels or as meaningful images; but it will suspicion and increase interception risk during transmission of the shares. Hence, VSS schemes have limitation that it suffers from a transmission risk problem for the secret itself and for the participants who are involved in the VSS scheme. To overcome the problem of transmission risk, we proposed a natural image based VSS scheme (NVSS scheme) which can shares secret images via different carrier media to protect the secret and the participants during the transmission phase. The above proposed (n, n) - NVSS scheme can share digital secret image over n-1 arbitrary selected natural images (called natural shares) and one noise-like share. The natural shares or natural images can be photos or hand-painted pictures in digital form or in printed form. The shares that look like noisy share can be generated based on these natural shares and the secret image. The unaltered natural shares are various and inoffensive, thus considerably reducing the transmission risk problem.